Upaya Pencapaian Herd Immunity melalui Aksi Cepat Tanggap Vaksinasi Covid -19 Dipoltekkes Sorong - Vera Iriani Abdullah (Yayasan Pendidikan Penelitian Pengabdian Algero, 2022)
At the end of 2020 and early 2021 the Covid-19 vaccine has been approved for general use in various countries. The level of public doubt about the covid-19 vaccination is generally growing throughout the world and is quite influencing people's motivation to get vaccinated. The low level of acceptance of the COVID-19 vaccine is due to indecision, it is evident that the level of indecision for Covid-19 vaccination differs across the world based on perceptions of susceptibility and severity of Covid-19 and demographic characteristics of society such as gender, age, education, income, and population. profession. Efforts to optimize vaccination achievements are contained in the Presidential Regulation which was signed on October 6, 2020 regarding the procurement of vaccines and the implementation of the vaccination program to tackle the covid pandemic, so the government has seriously prepared the vaccination program carefully regarding its distribution and implementation. Vaccines are the most economical and effective way to prevent infectious diseases including COVID-19. The purpose of community service activities is to assist government programs in accelerating the implementation of COVID-19 vaccination, it is necessary to optimize the vertical technical implementation unit of the Ministry of Health including Poltekkes by achieving the vaccination target of 1 million doses/day. For this reason, as a lecturer, as a form of implementation of the tri dharma, universities are encouraged to take an active role in Covid-19 vaccination activities according to the Decree of the Director of the Sorong Health Polytechnic regarding the determination of the vaccination team as a form of community service. The method of implementing activities directly in the field is in the form of health services. The location of the activity is at the Poltekkes vaccination center of the Ministry of Health, Sorong, Jalan Basuki rachmat Km. 11.5 Sorong West Papua. The target is all people of Sorong City and Sorong Regency who have not received vaccinations.